(untitled) (Journal of Information Technologies in Education (ITE), 2015)
During 15 years the Institute of Information technology and training of NAPS of Ukraine carries out research work aimed at solving actual problems of the creation, implementation and use of ICT in education, construction and development of computer-based learning environment of open education and e-learning, electronic educational resources, managing and supporting of the researches, technologies of cloud computing. The article considers the main activities of the Institute of Information Technologies and Learning Tools of NAPS of Ukraine. The experience of actual pedagogical issues developing,cooperation among research institutions and universities within activities of joint research laboratories, are reflected. The prospective research directions that will contribute to the modernization and further development of modern learning and scientific environment of educational institutions of Ukraine, in particular, the introduction of cloud oriented tools and technologies, the learning e-resources quality assurance, are outlined. The aim of the paper is to outline the main activities of the Institute of Information technology and training of NAPS of Ukraine during last 15 years and reflect the experience and perspectives of scientific and pedagogical cooperation of national research institutions and universities.